How the mouse got its stripes - Maini, P (2003)
Acentral issue in developmental biology is the understanding of how various processes interact to produce spatio-temporal patterns in the embryo. To even observe these dynamical patterns directly is a challenge and, although technological advances in, for example, imaging techniques are beginning to address this problem, it is still far from trivial. A new strain of mouse that is deficient in hair formation (1) now makes it possible to visualize directly traveling waves of pigmentation propagating over the skin of the mouse. This new study adds an extra dimension to the challenge of elucidating the mechanisms that underlie embryonic pattern formation and provides further evidence for self-organization. From an apparently homogeneous mass of dividing cells in the very early stages of development emerges the vast and sometimes spectacular array of patterns and structures observed in animals. The mechanisms underlying the coordination required for cells to produce pattern on a spatial scale much larger than a single cell is still largely a mystery, despite a huge amount of experimental and theoretical research. There is inherent in the oocytes positional information that must guide pattern, but cells that are completely dissociated and randomly mixed can recombine to form periodic spatial structures (2). This leads to the intriguing possibility that at least some aspects of spatio-temporal patterning in the embryo arise from the process of self-organization. The mathematician Alan Turing first proposed such a mechanism in his seminal 1952 article (3), in which he showed that a system of chemicals could evolve spontaneously into a spatial pattern. He further hypothesized that if these chemicals, which he termed morphogens, cued cell differentiation, then the patterns we see in nature would be the interpretation of chemical prepatterns. One year earlier, the Russian chemist Belousov showed experimentally that a system of . . .